Osteomyelitis caused by Sporothrix schenckii in an immunocompetent patient - Ferreira,Laura Cunha (2016)
Abstract Sporotrichosis is the most common subcutaneous mycosis in South America and its association with zoonotic transmission remains a relevant public health problem in Rio de Janeiro, Brazil. The disease most commonly presents as subacute or chronic cutaneous lesions, although dissemination to various organs and systems occurs in rare cases, mainly in immunosuppressed individuals. This report describes a case of sporotrichosis with severe bone and subcutaneous damage in an immunocompetent patient who did not exhibit the characteristic skin lesions of sporotrichosis, including ulcers, nodules, and lymphangitis.